2023
DOI: 10.1039/d2nj04211h
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of carbon dots prepared from collagen peptides using conventional hydrothermal and microwave methods

Abstract: Fish scale collagen peptide was used as a precursor to prepare carbon dots using conventional hydrothermal (CDs-HT) and microwave methods (CDs-MW). The optical properties of CDs prepared using the two...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…172 This unique phenomenon was explained by the generation of ˙OH radicals, which effectively destroyed the surface emissive centers in N-CDs (responsible for their emission) rather than the nuclear states (mainly cause absorption). The recently reported doped CDs from crayfish shell, 186,187 milk powder, 200 fish scales, 231 and fish scale collagen peptides 234 also showed excellent photo-stability. The photo-stability of animal/human biomass-derived CDs was also demonstrated for different period of times in air 134,150,172,174,183,247 and even after storage for many days/months/year under ambient conditions.…”
Section: Physiochemical Properties Of Animal/human Biomass-derived Cdsmentioning
confidence: 98%
See 2 more Smart Citations
“…172 This unique phenomenon was explained by the generation of ˙OH radicals, which effectively destroyed the surface emissive centers in N-CDs (responsible for their emission) rather than the nuclear states (mainly cause absorption). The recently reported doped CDs from crayfish shell, 186,187 milk powder, 200 fish scales, 231 and fish scale collagen peptides 234 also showed excellent photo-stability. The photo-stability of animal/human biomass-derived CDs was also demonstrated for different period of times in air 134,150,172,174,183,247 and even after storage for many days/months/year under ambient conditions.…”
Section: Physiochemical Properties Of Animal/human Biomass-derived Cdsmentioning
confidence: 98%
“…Fish scales of grass carp, [222][223][224] crucian carp, 225 Lethrinus lentjan, 226 Ctenopharyngodon idella, 227 Dicentrarchus labrax, 228,229 Labeo rohita, 230 and silver carp 231 have been employed in the synthesis of heteroatom-containing CDs using the HT or MW synthetic protocol (Table 1). Besides sh scale, other sh byproducts such as shark cartilage, 232 carp roe, 233 and sh scale collagen peptides 234 have also been employed to produce doped CDs. Table 1 clearly indicates that the QY of sh scale-derived doped CDs can reach up to 19.92%.…”
Section: Animal-derived Precursorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other methods, the hydrothermal method is preferred as it provides control over the crystal size, morphology, high purity and versatility and is an energy-efficient process. 27 A. M. Zardkhoshoui et al developed the NiGa 2 S 4 -rGO pseudocapacitive electrode material via a hydrothermal method, and it possessed a C s of 2124 F g −1 with a 73% retention of capacitance. 28 S. Arunpandiyan et al fabricated the ZnO/NiO:rGO nanocomposite through a hydrothermal route and demonstrated a C s of 622.3 F g −1 in 1 M potassium hydroxide.…”
Section: Introductionmentioning
confidence: 99%
“…27 A. M.Zardkhoshoui et al developed the NiGa 2 S 4 -rGO pseudocapacitive electrode material via a hydrothermal method, and it possessed a C s of 2124 F g −1 with a 73% retention of capacitance. 28 S. Arunpandiyan et al fabricated the ZnO/NiO:rGO nanocomposite through a hydrothermal route and demonstrated a C s of 622.3 F g −1 in 1 M potassium hydroxide.…”
mentioning
confidence: 99%